The Politics of Diversity in Music Education - Kallio, Alexis Anja; Westerlund, Heidi; Karlsen, Sidsel; Marsh, Kathryn; Sæther, Eva (Landscapes: the Arts, Aesthetics, and Education, 2021)
This open access book examines the political structures and processes that frame and produce understandings of diversity in and through music education. Recent surges in nationalist, fundamentalist, protectionist and separatist tendencies highlight the imperative for music education to extend beyond nominal policy agendas or wholly celebratory diversity discourses. Bringing together high-level theorisation of the ways in which music education upholds or unsettles understandings of society and empirical analyses of the complex situations that arise when negotiating diversity in practice, the chapters in this volume explore the politics of inquiry in research; examine music teachers' navigations of the shifting political landscapes of society and state; extend conceptualisations of diversity in music education beyond familiar boundaries; and critically consider the implications of diversity for music education leadership. Diversity is thus not approached as a label applied to certain individuals or musical repertoires, but as socially organized difference, produced and manifest in various ways as part of everyday relations and interactions. This compelling collection serves as an invitation to ongoing reflexive inquiry; to deliberate the politics of diversity in a fast-changing and pluralist world; and together work towards more informed and ethically sound understandings of how diversity in music education policy, practice, and research is framed and conditioned both locally and globally. "While many titles have addressed issues of diversity in its many forms, and while political issues are often embedded in this work, the current title specifically and directly frames the book from the perspective of politics, adding a unique focus and frame that makes an important contribution to the field. Addressing the politics of diversity as part of the "everyday processes by which we all exercise agency, negotiate power and identity, and assign meaning to difference" makes for compelling reading, offering a complex set of views on a dynamic and varied range of topics. This is a must read book to all compelled to engage with the urgent work around equity and diversity." - Patrick Schmidt, Professor of Music Education, Western University, Canada.